A 1 THz Schottky transceiver front‐end based on 5 μm GaAs monolithic membrane. Issue 12 (24th August 2022) - He, Yue; Li, Li; Liu, Ge; Tian, Yaoling; Zhou, Ren; Su, Wei
Abstract: A Schottky diode‐based 1 THz Schottky transceiver front end is designed, fabricated, and measured. The terahertz mixer and tripler are fabricated with a 5 μm‐thick GaAs monolithic Schottky technology. Compact passive filter and matching network are designed to reduce the loss of transmission route. At 300 K ambient temperature, the measured minimum double‐side band noise temperature and conversion loss of 1 THz subharmonic mixer are <5000 K and 13 dB, respectively. At self‐developed available pump source, the measured maximum output power of 1 THz monolithic tripler is over 70 μW and the average output power from 960 to 1030 GHz is 35 μW. The accomplished 1 THz monolithic circuits have proved the feasibility of the proposed design process, which have certain reference value for higher frequency solid‐state Schottky‐based circuit.